Factors influencing the choice of marketing channel by rice producers: evidence from the Mekong Delta Region, Vietnam. (25th November 2021) - Ho, Tien D.N.; Kuwornu, John K.M.; Tsusaka, Takuji W.; Nguyen, Loc T.; Datta, Avishek
The study examined the factors influencing the choice of rice marketing channel by smallholder rice producers in the Mekong Delta Region (MDR) of Vietnam. A multistage sampling technique was used to collect data from 405 rice producers in three provinces, namely, Can Tho, Dong Thap, and Tien Giang. The empirical results from the logit regression model reveal that distance to markets, asset endowment, farm size, sales quantity, price of rice, contract farming, organisational membership, access to credit, extension services, access to transportation, and storage facilities, influenced farmers' choice between direct and indirect channels. The findings suggest that policies should aim at setting up the appropriate floor price, improving transport infrastructure, providing formal credit and input subsidy, supporting farmer organisations, and strengthening extension services to help these farmers improve their livelihoods.